Regional Groundwater Quality Management through Hydrogeological Modeling in LCC, West Faisalabad, Pakistan - Aamir Shakoor; Zahid Mahmood Khan; Muhammad Arshad; Hafiz Umar Farid; Muhammad Sultan; Muhammad Azmat; Muhammad Adnan Shahid; Zafar Hussain (Journal of Chemistry)
The intensive abstraction of groundwater is causing a number of problems such as groundwater depletion and quality deterioration. To manage such problems, the data of 256 piezometers regarding groundwater levels and quality were acquired for the period of 2003 to 2012 in command area of Lower Chenab Canal (LCC), West Faisalabad, Pakistan. MODFLOW and MT3D models were calibrated for the period of 2003–2007 and validated for years 2008–2012 with respect to observed groundwater levels and quality data, respectively. After the successful calibration and validation, two pumping scenarios were developed up to year 2030: Scenario I (increase in pumping rate according to the historical trend) and Scenario II (adjusted canal water supplies and groundwater patterns). The predicted results of Scenario I revealed that, up to year 2030, the area under good quality groundwater reduced significantly from 50.35 to 28.95%, while marginal and hazardous groundwater quality area increased from 49.65 to 71.06%. Under Scenario II, the good quality groundwater area increased to 6.32% and 12.48% area possesses less hazardous quality of groundwater. It was concluded that the canal water supply should shift from good quality aquifer zone to poor quality aquifer zone for proficient management of groundwater at the study area.